Efeito do pó de rocha de basalto, cama de frango e esterco bovino nos atributos químicos do solo, teores de nutrientes foliares e produtividade da soja e milho segunda safra - Ribeiro, Luane Laíse Oliveira (2023)
The objective of this work was to evaluate the effect of doses of basalt rock powder associated with poultry litter and cattle manure on soil chemical attributes, leaf nutrient content and productivity of soybean and corn second crop, with reference to fertilization soluble chemical fertilizer (NPK). The experiment was conducted in randomized blocks (DBC), in a factorial arrangement (5x2) + 1, with four replications. Five doses of basalt rock dust (0, 4, 8, 12 and 16 t ha-1) associated with two sources of animal waste were used: bovine manure and poultry litter (5 t ha-1). In the additional treatment, soluble chemical fertilizer was used with 300 kg ha-1 of commercial formula 02-20-18 (NPK) for soybean and 285 kg ha-1 (12-24-12 NPK) for corn second crop. The contents of foliar nutrients were evaluated: N, P, K, Ca and Mg; Soil chemical attributes: acidity (pH, H+Al), Organic Carbon (CO), Exchangeable Bases (Ca, Mg and K), Cation Exchange Capacity (CEC) and Available Phosphorus (P) in layers of 0.00 – 0.05 m; 0.05– 0.10 m and 0.10 – 0.20 m; in addition to soybean and second-crop corn productivity. The doses of basalt in association with poultry litter and cattle manure provided positive results in the levels of foliar nutrients in soybeans and second-crop corn, as well as in the chemical attributes of the soil, presenting levels within the recommended range for good growth and development of crops. The productivity of soybean cultivated with basalt and chicken litter was on average 3,462.8 kg ha-1 and with cattle manure it was 3,439.2 kg ha-1. In corn second crop, the highest productivity was verified at the basalt dose of 3.7 t ha-1 with chicken litter (5,154.7 kg ha-1) and at the dose of 3.1 t ha-1 with manure cattle (5,207.7 kg ha-1). The experimental research demonstrated that the results of the evaluated characteristics under the effect of basalt, chicken litter and bovine manure doses were the same as those observed when soluble chemical fertilization (NPK) was used. In view of this, basalt rock dust associated with organic residues of animal origin can be recommended and used to improve the chemical attributes of the soil and as an alternative and complementary source of fertilizer for crops, contributing to greater sustainability of agricultural production systems.